Has Uber Made It Easier to Get a Ride in the Rain? - Abel Brodeur; Kerry Nield (Institute for the Study of Labor (IZA), 2016)
In New York City (NYC), it has been a common complaint that it is difficult to find a taxi in the rain. Using all Uber rides in NYC from April to September 2014 and January to June 2015, we show that the number of Uber rides is significantly correlated with whether it rained. The number of Uber rides per hour is about 25 percent higher when it is raining, suggesting that surge pricing encourages an increase in supply. During the same time period, the number of taxi rides per hour increases by only 4 percent in rainy hours. We then show that the number of taxi rides per hour decreased by approximately 8 percent after Uber entered the New York market in May 2011, confirming that Uber is depressing taxi demand. Last, we test whether the total (Uber plus taxi) number of rides in rainy hours increased since May 2011. Our estimates suggest that the total number of rides increased by approximately 9 percent since Uber entered the market and that it is relatively easier to get a ride in rainy than in non-rainy hours in post-Uber years.
Keywords: D01; D03; L92; J22; 330; rain; Uber; taxi; dynamic pricing